Erbium–doped nanoparticles in silica–based optical fibres. (7th February 2012) - Blanc, Wilfried; Mauroy, Valérie; Dussardier, Bernard
Developing of new rare–earth (RE)–doped optical fibres for power amplifiers and lasers requires continuous improvements in the fibre spectroscopic properties (like shape and width of the gain curve, optical quantum efficiency, resistance to spectral hole burning and photodarkening...). Silica glass as a host material for fibres has proved to be very attractive. However, some potential applications of RE–doped fibres suffer from limitations in terms of spectroscopic properties resulting from clustering or inappropriate local environment when doped into silica. To this aim, we present a new route to modify some spectroscopic properties of RE ions in silica–based fibres based on the incorporation of erbium ions in amorphous dielectric nanoparticles, grown in–situ in fibre preforms. By adding alkaline earth elements, in low concentration into silica, one can obtain a glass with an immiscibility gap. Then, phase separation occurs under an appropriate heat treatment. We investigated the role of three alkaline–earth elements: magnesium, calcium and strontium. We present the achieved stabilisation of nanometric erbium–doped dielectric nanoparticles within the core of silica fibres. We present the nanoparticle dimensional characterisation in fibre samples. We also show the spectroscopic characterisation of erbium in preform and fibre samples with different compositions. This new route could have important potentials in improving RE–doped fibre amplifiers and laser sources.